REVITALISASI TRADISI MEMACE SEBAGAI INSTRUMEN PRESERVASI NASKAH LONTAR RENGGANIS DAN PENCEGAHAN PERNIKAHAN USIA ANAK DI LOMBOK - Andi Muhammad Aminullah; Muhamad Khalid Iswadi; Syahrul, Syahrul (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to examine the revitalization of the Memace tradition as an instrument for preserving the ancient manuscript Lontar Rengganis as well as an educational medium for preventing child marriage in Lombok. Using a qualitative approach with a phenomenological method, this research explores the meaning and subjective experiences of the community regarding the Memace practice, particularly within the socio-cultural context of the Sasak people. Data were collected through in-depth interviews, participatory observation, and cultural documentation. The findings reveal that Memace is a form of oral cultural transmission rich in moral, spiritual, and educational values. The narratives in Lontar Rengganis implicitly reject child marriage by emphasizing the importance of education and female empowerment. The revitalization of Memace not only contributes to the physical and cultural preservation of the manuscript but also strengthens collective awareness around child protection issues. This tradition has proven to be an effective medium of cultural communication and can be developed as a model of community-based archival preservation (preservation through use) and a culturally rooted instrument for social advocacy.